Los sueños, fantasías y vivencias como poética personal para una representación pictórica surrealista (onírico-metafísico) - Soto Villacis, Karla Jackeline (2019)
The present investigation entitled THE DREAMS, FANTASIES AND VIVENCES AS PERSONAL POETRY FOR A SURREALISTIC PICTORIAL REPRESENTATION (ONÍRICO-METAFÍSICO)., raises the analysis of the Surrealist artistic current in the oniric-metaphysical painting to generate a pictorial proposal based on dreams, fantasy and personal experiences as a management motive, where images of reality are taken up and re-contextualized. For the development of it, different research methods are used according to each one of the project phases, among them are: the deductive that starts from the concepts about surrealism to base the proposal; the inductive that through the observation, experimentation and artistic referents structure the proposal in its pre-production-production and post-production phases; theories that reinforce the research among them, the surrealist aesthetics, the manifesto of André de Breton, the study on the dreams of Sigmund Freud and on the unconscious, which are necessary for the pictorial proposal are retaken. All this theoretical and practical structure generate a pictorial proposal that originates in experience, experiences, dreams and personal fantasies, where the image can be contextualized, decontextualized and re-contextualized to a reality according to a criterion or a personal vision